The therapeutic potential of phytol towards Trypanosoma congolense infection and the inhibitory effects against trypanosomal sialidase - Saad, Saad Bello; Ibrahim, Mohammed Auwal; Jatau, Isa Danladi (Elsevier, 2020)
The search for novel therapeutic candidates against animal trypanosomiasis is an ongoing scientific endevour because of the negative impacts of the disease to the African livestock industry. In this study, the in vivo ther apeutic potentials of phytol toward Trypanosoma congolense infection and the inhibitory effects on trypanosomal sialidase were investigated. Rats were infected with T. congolense and administered daily oral treatment of 50 and 100 mg/kg BW of phytol. Within the first 10 days of the treatment, no antitrypanosomal activity was recorded but a moderate trypanostatic activity was observed from day 17-day 21 pi. However, at 100 mg/kg BW, phytol demonstrated a significant (p < 0.05) ameliorative potentials toward T. congolense-induced host-associated pathological damages such as anaemia, hepatic and renal damages; and the data was comparable to dimina zine aceturate. Moreover, the T. congolense caused a significant (p < 0.05) increase in free serum sialic acid level which was significantly (p < 0.05) prevented in the presence of phytol (100 mg/kg BW). In an in vitro analysis, phytol inhibited partially purified T. congolense sialidase using an uncompetitive inhibition pattern with inhi bition binding constant of 261.24 μmol/mL. Subsequently, molecular docking revealed that the compound binds to homology modelled trypanosomal sialidase with a binding free energy of
Keywords: Anaemia; Animal trypanosomosis; Host-associated damages; Phytol; Sialidase; Trypanosoma congolense; ACENTDFB; Ahmadu Bello University; ACE: Neglected Tropical Diseases and Forensic Biotechnology